Association Between Micronutrient Concentrations and Human Epididymis Protein 4 - Lim ZW (Dove Medical Press, 2021)
Zhu Wei Lim,1 Wei Liang Chen2 1Department of Obstetrics and Gynecology, Changhua Christian Hospital, Changhua, Taiwan; 2Division of Geriatric Medicine, Department of Family and Community Medicine, Tri-Service General Hospital and School of Medicine, National Defense Medical Center, Taipei, TaiwanCorrespondence: Wei Liang ChenDivision of Geriatric Medicine, Department of Family and Community Medicine, Tri-Service General Hospital and School of Medicine, National Defense Medical Center, Taipei, TaiwanTel +886-2-87923311 ext. 16567Fax +886-2-87927057Email weiliang0508@gmail.comBackground: Human epididymis protein 4 (HE4) has been frequently used to study in many malignant tumors, while serum nutritional markers are used to determine a person’s health status. However, the link between serum micronutrient concentrations and HE4 has not yet been clarified.Methods: A total of 2464 eligible female participants and serum concentrations of nutritional biomarkers were chosen from the National Health and Nutrition Examination Surveys (NHANES) 2001– 2002. For statistical analysis, we used the χ2 test, multivariable linear regression, and analysis of variance. Adjusted models were used, and the concentrations of serum nutritional biomarkers were divided into quartiles.Results: The mean age of the participants was 48.07 years. Among twelve micronutrients, five were negatively associated with HE4 in models 1, 2 and 3. Only α-carotene, trans-β-carotene, cis-β-carotene, trans-lycopene and retinol were associated with HE4, with beta coefficients of − 0.102, − 0.027, − 0.506, − 0.131 and − 0.054, respectively. After performing quartile-based analysis, statistical significance was only found for serum α-carotene, trans-lycopene, and retinol in the three models. In model 3, the beta coefficients [95% confidence intervals (CIs)] of the fourth quartiles compared to the first quartiles for α-carotene, trans-lycopene, and retinol were − 3.390 (− 5.053, − 1.727), − 4.036 (− 5.722, − 2.351) and − 4.146 (− 5.899, − 2.393), respectively. Serum concentrations of these three nutritional biomarkers were inversely related to serum HE4 concentration (p trend < 0.001).Conclusion: HE4 is a useful and novel biomarker that can be used with many diseases, especially ovarian cancer. Three of our selected micronutrients were inversely associated with HE4 concentration. Supplement of micronutrients may reduce the levels of HE4 and the subsequent of ovarian cancer’s risk. Therefore, a formula that correlates HE4 with nutritional biomarkers needs to be established before use in clinical applications.Keywords: human epididymis protein 4, vitamin A, vitamin E, carotenoids